Enhancing CO2/CH4 and CO2/N2 separation performances of ZIF-8 by post-synthesis modification with [BMIM][SCN]. (15th November 2018) - Zeeshan, Muhammad; Keskin, Seda; Uzun, Alper
Graphical abstract: 1- n -Butyl-3-methylimidazolium thiocyanate ([BMIM][SCN]) was incorporated into a zeolitic imidazolate framework (ZIF-8) to examine CO2 /CH4 and CO2 /N2 separations. Abstract: Ionic liquid (IL)-incorporated metal organic frameworks (MOFs) are promising materials for gas adsorption and separation processes. In this work, 1- n -butyl-3-methylimidazolium thiocyanate ([BMIM][SCN]) was incorporated in a zeolitic imidazolate framework (ZIF-8) to examine the adsorption and separation of different gases. X-ray diffraction (XRD) and scanning electron microscopy (SEM) results confirmed that ZIF-8 retains its structural integrity in the IL-incorporated sample. The Brunauer–Emmett–Teller (BET) surface area and pore volume of the IL-incorporated sample decreased significantly indicating the IL confinement into the MOF. Results of thermogravimetric analysis (TGA) demonstrate changes in the decomposition temperatures of both bulk IL and pristine ZIF-8 when the IL was incorporated into the MOF pores. Fourier transform infrared (FTIR) spectroscopy was performed to confirm the presence of interactions and successful incorporation of IL into MOF. Gas adsorption isotherms of CO2, CH4, and N2 were measured for pristine ZIF-8 and IL-incorporated ZIF-8. The uptake amounts for each gas decreased as compared to their values on pristine ZIF-8, however, the decrease in the CO2 uptake was less compared to CH4 and N2 . The IL-incorporated sample exhibited approximately 2.6-times higher ideal selectivity for CO2 /CH4 and four-times higher ideal selectivity for CO2 /N2 at 1 mbar than their corresponding values for pristine ZIF-8. These results indicate that IL-MOF combinations offer a huge potential for gas separations.